An evidenced‐based strategy for timely delivery of clinical letters. Issue 1 (March 2017) - Corson, Eve; Hargreaves, Claire; Grimshaw, Sarah; Wiggans, Joanna; Mitchell, Sarah; Toon, Ruth; Palmer, Claire; Cox, David; Pretorius, Charlotte; Wilkinson, Ellen; Laugharne, Richard; Shankar, Rohit
Abstract : In the UK, clinical letters are the most common way for doctors to communicate information about patients but no identified national standards exist on how soon non‐urgent clinical letters should be dispatched. Here, Dr Shankar and colleagues discuss their audit of time taken for GPs to receive a clinic letter and suggest ways for improving practice.